Prevalencia del síndrome de burnout en internos de medicina del Hospital Militar Central de Lima - Arias, Renzo (2018)
ABSTRACT Objective: To determine prevalence and associated factors of Burnout Syndrome in medicine interns. Methods: Analytical cross-sectional study. Maslach Burnout Inventory and a Sociodemographic Variables and Associated Factors questionnaire, were applied. The study was carried out at Hospital Militar Central "Coronel Luis Arias Schreiber", October 2016. Results: The prevalence of Burnout Syndrome was established at 5.2 % (n= 5). 27.1 % (26), 13.4 % (13) and 20.8 % (20), had high levels of emotional exhaustion and depersonalization and low levels of personal accomplishment, respectively. A statistically significant association was established between the living alone variable and emotional exhaustion (p= 0,046) and with depersonalization (p= 0.018). We found an association between working more than 50 hours per week and Burnout Syndrome (p= 0,038). Conclusion: The prevalence of Burnout Syndrome in medicine interns at Hospital Militar Central "Coronel Luis Arias Schreiber" is low. To live alone was associated with emotional exhaustion and depersonalization. An association between Burnout Syndrome and work hour per week was found.